Model Sinergi Self-Regulated Learning dan Community of Inquiry pada Platform Merdeka Mengajar untuk Pengembangan Profesionalitas Guru - Selviana Haenkanes Turot; Dinn Wahyudin (CV. Global Cendekia Inti, 2026)
The discourse on teacher professional development frequently separates individual agency from the dynamics of community support within digital environments, even though their integration is vital to mitigating professional isolation and cognitive exhaustion. Aligning personal and social dimensions is essential for ensuring the sustainability of digital transformation in schools. The use of the Merdeka Mengajar Platform (PMM) often relies on individual independence, which poses risks of professional isolation and cognitive fatigue. This study aims to evaluate PMM's effectiveness within the Indonesian Teacher Professional Education (PPG) program by synthesizing literature through the dual lenses of Self-Regulated Learning (SRL) and Community of Inquiry (CoI). Using a Systematic Literature Review (SLR) method with the PRISMA protocol, 110 peer-reviewed journal articles addressing SRL and CoI in the PPG context from the Google Scholar database (2022–2026) were analyzed in depth. Findings indicate that literature focus is divided into four categories: SRL studies (36%), CoI (26%), systemic barriers (24%), and SRL-CoI synergy (14%). Analysis reveals that although personal cognitive agency (SRL) is a vital initiator, platform effectiveness reaches its optimum when synergized with social and teaching presence (CoI) through local learning groups. This synergy demonstrates effectiveness in mitigating technostress and digital administrative burdens. The study indicates that digital transformation in education can integrate individual independence with strong community support to ensure the sustainability of humanistic teacher professionalism.